Comparison of Effectiveness Cost Therapy and Increasing Level of Haemoglobin, Ferritin in Pregnant Women with Anemia Whom Are Given Iron Tablet Everyday and Every Two Days - Irawan, Agung Pramartha; Pramono, M. Besari Adi; Wijayanti, Asih (Medica Hospitalia : Journal of Clinical Medicine, 2026)
BACKGROUND: Anemia is common in pregnancy, with a prevalence of 48.9% in Indonesia (Riskesdas 2018). It increases the risk of impaired fetal growth, stunting, and intellectual disorders. Iron supplementation, as recommended by Permenkes No. 88/2014, is a key preventive strategy. Evidence such as Moretti et al. (2015), suggests that alternate-day supplementation improves absorption due to reduced hepcidin activity. AIM: To evaluate the effectiveness of administering iron tablets every two days in terms of treatment cost, increases in hemoglobin (Hb) and ferritin levels, and incidence of gastrointestinal adverse effects. METHODS: This was a true experimental study using a randomized pre–post test control group design. The control group received iron tablets daily for two months, while the intervention group received iron tablets every two days. The study was conducted at the Obstetrics and Gynecology Polyclinic of Kariadi Central General Hospital and Halmahera Primary Health Care over eight months (December 2023 – July 2024). Each group included 23 subjects. Body weight, hemoglobin, and ferritin were measured at baseline and after two months. Adverse effects and neonatal outcomes were also documented. RESULTS: Baseline characteristics were normally distributed. The intervention group showed a significant increase in hemoglobin and ferritin levels, higher neonatal birth weight, and lower treatment cost and adverse effects compared to the control group (p < 0.05). Post-treatment differences between groups were 0.5 g/dL for hemoglobin and 17.2 ng/mL for ferritin. CONCLUSION: Administering iron tablets every two days is effective in improving hemoglobin and ferritin levels in pregnant women with anemia and is also cost-effective with fewer adverse effects.